Haloperidol affects coupling between QT and RR intervals in guinea pig isolated heart - Petr Vesely; Tibor Stracina; Miroslava Hlavacova; Josef Halamek; Jana Kolarova; Veronika Olejnickova; Veronika Mrkvicova; Hana Paulova; Marie Novakova (Elsevier, 2019)
Prolonged QT interval is an independent risk factor for development of ventricular arrhythmias. Haloperidol is one of the drugs inducing QT prolongation. Previous studies showed that haloperidol affects not only QT duration but also heart rate (RR interval). The present work focused on relationship between QT and RR and its changes under acute and chronic haloperidol administration. The study included 14 male guinea pigs divided into control and haloperidol-treated group. After 21-days administration of haloperidol or vehiculum, electrograms in isolated hearts were recorded. QT/RR and dQT/dRR coupling were calculated. Chronic haloperidol administration significantly decreases the coupling between QT and RR. Acute haloperidol exposure significantly decreases the dQT/dRR coupling in both treated and untreated guinea pig hearts. Flatter QT/RR relationship reveals a lack of QT adaptation to increased heart rate. It should be emphasized that in such situation ECG recording will not show significant QT prolongation evaluated according to clinical rules. However, if QT interval does not adapt to increased heart rate sufficiently, the risk of ventricular arrhythmias may be increased despite practically normal QT interval length. The results are supported by findings in biochemical analyses, which proved eligibility of the used model. Keywords: Drug-induced QT prolongation, Guinea pig, Haloperidol, Isolated heart, QT/RR coupling